SIBS triblock copolymers in cardiac surgery: in vitro and in vivo studies in comparison with ePTFE - M. A. Rezvova (Vestnik Transplantologii i Iskusstvennyh Organov, 2020)
Implantation of polymeric heart valves can solve the problems of existing valve substitutes – mechanical and biological. Objective: to comprehensively assess the hemocompatibility of styrene-isobutylene-styrene (SIBS) triblock copolymer, synthesized by controlled cationic polymerization in comparison with expanded polytetrafluoroethylene (ePTFE) used in clinical practice. Materials and methods. SIBS-based films were made by polymer solution casting method; in vitro biocompatibility assessment was performed using cell cultures, determining cell viability, cell adhesion and proliferation; tendency of materials to calcify was determined through in vitro accelerated calcification; in vivo biocompatibility assessment was performed by subcutaneous implantation of rat samples; hemocompatibility was determined ex vivo by assessing the degree of hemolysis, aggregation, and platelet adhesion. Results. The molecular weight of synthesized polymer was 33,000 g/mol with a polydispersity index of 1.3. When studying cell adhesion, no significant differences (p = 0.20) between the properties of the SIBS polymer (588 cells/mm2) and the properties of culture plastics (732 cells/mm2) were discovered. Cell adhesion for the ePTFE material was 212 cells/mm2. Percentage of dead cells on SIBS and ePTFE samples was 4.40 and 4.72% (p = 0.93), respectively, for culture plastic – 1.16% (p < 0.05). Cell proliferation on the ePTFE surface (0.10%) was significantly lower (p < 0.05) than for the same parameters for SIBS and culture plastic (62.04 and 44.00%). Implantation results (60 days) showed the formation of fibrous capsules with average thicknesses of 42 μm (ePTFE) and 58 μm (SIBS). Calcium content in the explanted samples was 0.39 mg/g (SIBS), 1.25 mg/g (ePTFE) and 93.79 mg/g (GA-xenopericardium) (p < 0.05). Hemolysis level of red blood cells after contact with SIBS was 0.35%, ePTFE – 0.40%, which is below positive control (p < 0.05). Maximum platelet aggregation of intact platelet-rich blood plasma was 8.60%, in contact with SIBS polymer – 18.11%, with ePTFE – 22.74%. Conclusion. In terms of hemocompatibility properties, the investigated SIBS polymer is not inferior to ePTFE and can be used as a basis for development of polymeric prosthetic heart valves.